Purple Yam (Dioscorea alata) Extract Increasing Dopamine Levels and Improving the Brain's Microscopic Features in Parkinson's Model Mice - Yuliani, Sapto; Utami, Dwi; Nurani, Laela Hayu; Ramadhan, Muhammad Marwan; Ainiyah, Nadia Putri; Bachri, Mochammad Saiful; Widyaningsih, Wahyu; Amukti, Danang Prasetyaning (Borneo Journal of Pharmacy, 2025)
Parkinson's disease (PD) is a severe neurodegenerative disorder, that causes progressive motor issues from the loss of dopamine-producing neurons in the substantia nigra pars compacta (SNpc). Purple yam (Dioscorea alata), rich in anthocyanins, shows promise as a natural antioxidant and neuroprotectant. This study investigated the antiparkinsonian effects of D. alata extract on dopamine levels and brain microscopic features in a haloperidol-induced PD mouse model. Thirty-five male mice were randomly allocated into seven groups: normal (CMC-Na and aqua pro injection), haloperidol-induced negative control (CMC-Na), positive control (levodopa 39 mg/kgBW), curcumin (200 mg/kgBW), and D. alata extract-treated groups (100, 200, and 400 mg/kgBW). Treatments were administered daily for seven days. On day 8, all groups, except the normal control, received an intraperitoneal injection of haloperidol (2 mg/kgBW) to induce Parkinsonism. Three hours post-haloperidol injection, dopamine levels were measured from orbital vein blood. Subsequently, brains were harvested for histological examination of the SNpc using Toluidine blue staining. Data were statistically analyzed using one-way ANOVA followed by LSD post-hoc tests. The 400 mg/kgBW dose of D. alata extracts significantly increased dopamine levels (p<0.05) compared to the negative control group. Microscopic analysis of the SNpc in mice treated with 400 mg/kgBW extract revealed preserved, dark, and solid neuronal morphology, with significantly higher scoring results (p<0.05) when compared to the levodopa-treated group. These findings suggest that D. alata extract, particularly at a dose of 400 mg/kgBW, exhibits potential antiparkinsonian activity by elevating dopamine levels and mitigating dopaminergic neuronal damage in a haloperidol-induced PD mouse model.